Synthesis of PLA/PLGA Biocomposite with Variation of Silane Coupling Agent as Reinforcement for Bone Plate Applications - Hartanto, Denny; Purniawan, Agung; Sutarsis, Sutarsis (Syntax Corporation, 2025)
This research investigated the synthesis of polylactic acid (PLA) and poly(lactic co-glycolic acid) (PLGA) bio-composites with nano-hydroxyapatite (nHA) fillers for bone plate applications, focusing on the effects of different silane coupling agents and polymer ratios. The research analyzed how various silane coupling agents (3-MPS, APTES, Vinyl Silane) and PLA compositions influenced structural, morphological, mechanical, biodegradation, and biocompatibility properties. Materials were characterized using FTIR, SEM, tensile and compression testing, weight loss analysis, and MTT assay. FTIR confirmed successful nHA surface modification with silane agents through the presence of Si-O-Si and NH2 functional groups. SEM revealed that Vinyl Silane produced samples with fewer voids and better filler distribution, while increased PLGA content resulted in more homogeneous structures. Mechanical testing demonstrated that composites with Vinyl Silane exhibited superior tensile (6.98 MPa) and compressive strength (8.19 MPa), while samples with 20% PLGA content achieved the highest values (7.18 MPa tensile, 8.28 MPa compressive). Biodegradation analysis showed that PPnHA8020-APTS samples achieved optimal degradation time (5.1 months), aligning with bone healing timelines. All bio composites demonstrated cell viability above 80%, exceeding ISO 10993-5 standards, with PPnHA9010-APTS showing the highest biocompatibility (86.76%). The research established that optimized PLA/PLGA/nHA bio composites, particularly with Vinyl Silane coupling agent and 20% PLGA content, offer promising properties for biodegradable bone implant applications, combining adequate mechanical strength with appropriate degradation rates and excellent biocompatibility.